Pola Pemikiran Imam Syafi’i Dalam Menetapkan Hukum Islam - Abdul Karim T (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2013)
Imam Shafi'i is a mujtahid/scholar who has created a masterpiece in the world of Islam. He is the first composer who determine the ushul fiqh as a discipline that can be used to Islamic law students. He is popular as a moderate thinkir where his thought that combining between who emphasise their thought in al-ra'y (logocal view) and sunnah/traditions. His main work in the field of jurisprudence, namely al-Risala and al-Umm. Imam Shafi’i’s thoght/ijtihad finally was formed as a mazhab in Islamic law/fiqhi.